Initial Experience of Spinal Cord Perfusion Pressure Goals in Lieu of Mean Arterial Pressure Goals in Acute Traumatic Spinal Cord Injury at a United States Level I Trauma Center: A Transforming Research and Clinical Knowledge-Spinal Cord Injury Study. (1st September 2019) - Yue, John K; Hemmerle, Debra P; Deng, Hansen; Winkler, Ethan A; Thomas, Leigh H; Fernandez, Xuan Duong; Upadhyayula, Pavan S; Kyritsis, Nikolaos; Pascual, Lisa U; Singh, Vineeta; Weinstein, Philip R; Talbott, Jason; et al.
Abstract: INTRODUCTION: Management of traumatic spinal cord injury (SCI) includes urgent decompression and decreasing secondary injury through blood pressure augmentation. Mean arterial pressure (MAP) targets have been the standard of care for decades, however recent clinical trial data have demonstrated the relationship between spinal cord perfusion pressure (SCPP) and neurologic recovery. These data led to implementation of a novel standard of care protocol at our institution focused on SCPP, in lieu of MAP goals. We provide the initial experience of implementation of protocolized SCPP goals for acute SCI at a US level I trauma center. METHODS: Starting December 2017, all moderate/severe blunt SCI patients at our institution presenting < 24 h of injury received lumbar subarachnoid drain placement (LSAD) for intraspinal pressure (ISP) and SCPP monitoring in the neurological intensive care unit (NICU), and were included in the Transforming Research and Clinical Knowledge in Spinal Cord Injury (TRACK-SCI) data registry. This is known as the SCPP Protocol, and comprises standard care at our institution. SCPPs were monitored for 5 d with goal = 65 mmHg achieved through intravenous fluids and vasopressor support. American Spinal Injury Association Impairment Scale (AIS) grades were assessed at admission and day 7. RESULTS: In 15 patients enrolled to date, age was 60.5 ± 17.0 yr and 46.7% were = 65. Injury level was 93.3% cervical and 6.7% thoracic. Admission AIS were 20.0%/20.0%/26.7%/33.3% for A/B/C/D, respectively. A total of 14 patients underwent surgical decompression with time to surgery 8.8 ± 7.1 h and 71.4% < 12 h. Hospital length of stay (LOS) was 14.7 ± 8.3 d. NICU LOS was 11.5 ± 8.9 d. No patient had lumbar drain-related complications. Seven patients had respiratory complications and 1 expired after family transitioned to comfort care. AIS grade improvement of 1 occurred in one-third of patients (2 AIS = B, 3 AIS = C). CONCLUSION: In our initial experience of 15 patients with acute traumatic SCI, standardized SCPP goal-directed care through lumbar ISP monitoring for the first 5 d postinjury was feasible and without SCPP-related complications.